2023
DOI: 10.3389/fpsyg.2022.1070742
|View full text |Cite
|
Sign up to set email alerts
|

Sense of agency predicts severity of moral judgments

Abstract: Sense of Agency (SoA) refers to the awareness of being the agent of our own actions. A key feature of SoA relies on the perceived temporal compression between our own actions and their sensory consequences, a phenomenon known as “Intentional Binding.” Prior studies have linked SoA to the sense of responsibility for our own actions. However, it is unclear whether SoA predicts the way we judge the actions of others – including judgments of morally wrong actions like harming others. To address this issue, we ran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Another explanation for the rigid moral judgment in OC patients could be their malfunctioning sense of agency. Spaccasassi et al (2023) revealed that people with stronger feelings of agency and responsibility for their own actions show strict moral evaluations of others' actions. In this line, Oren et al (2019) found that direct judgments of agency are higher in individuals with OCD.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the rigid moral judgment in OC patients could be their malfunctioning sense of agency. Spaccasassi et al (2023) revealed that people with stronger feelings of agency and responsibility for their own actions show strict moral evaluations of others' actions. In this line, Oren et al (2019) found that direct judgments of agency are higher in individuals with OCD.…”
Section: Discussionmentioning
confidence: 99%